ANALISIS KOMPETENSI LITERASI BACA TULIS KELAS 1 SDN BLABAK 1 - Herlina Putri, Sherly; Icha Hartanti, Levina; Laila, Alfi; Huliyyatul Maula, Saila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low literacy skills of early elementary school students, which remains a problem in the learning process. Reading and writing skills are an important foundation in supporting student learning success at the next level. This study aims to analyze the literacy skills of first-grade students at SDN Blabak 1 and identify obstacles experienced by students in the literacy learning process. The study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, initial reading and writing tests, teacher interviews, and documentation. The research subjects consisted of 14 first-grade students of SDN Blabak 1. The results showed that most students had literacy skills in the "Very Developed" category with achievements above 81%. Students were able to recognize vowels and consonants, read syllables and simple words, understand short readings, and write letters, words, and simple sentences independently. However, there were still some students who experienced difficulties in recognizing letters, reading fluently, and writing simple words. Factors that influence students' literacy skills include lack of practice at home, low self-confidence, and differences in students' learning abilities. Teachers' learning strategies through learning media, reading aloud, and reading habits are considered capable of helping students' literacy development.